2013
DOI: 10.1111/epi.12408
|View full text |Cite
|
Sign up to set email alerts
|

Automated hippocampal segmentation in patients with epilepsy: Available free online

Abstract: PurposeHippocampal sclerosis, a common cause of refractory focal epilepsy, requires hippocampal volumetry for accurate diagnosis and surgical planning. Manual segmentation is time-consuming and subject to interrater/intrarater variability. Automated algorithms perform poorly in patients with temporal lobe epilepsy. We validate and make freely available online a novel automated method.MethodsManual hippocampal segmentation was performed on 876, 3T MRI scans and 202, 1.5T scans. A template database of 400 high-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 28 publications
1
65
0
3
Order By: Relevance
“…The manual method uses visual identification of hippocampal margins, whereas FreeSurfer transforms the images to standard coordinates, and then utilizes voxel intensities and probabilities to delineate the hippocampus. A study using a different method found a good correlation between automated and manual hippocampal volume measurements, with a tendency for the former to be larger …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The manual method uses visual identification of hippocampal margins, whereas FreeSurfer transforms the images to standard coordinates, and then utilizes voxel intensities and probabilities to delineate the hippocampus. A study using a different method found a good correlation between automated and manual hippocampal volume measurements, with a tendency for the former to be larger …”
Section: Discussionmentioning
confidence: 99%
“…Recently, an automated segmentation algorithm was developed specifically for adult patients with epilepsy by using a template database comprising epilepsy patients with a range of pathologies rather than healthy subjects . Following alignment, segmentation is performed using a local ranking strategy .…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been developed to parcellate the whole brain, segmenting it into a large number of regions (Aljabar et al, 2008; Babalola et al, 2009; Fonov et al, 2012; Han et al, 2009; Heckemann et al, 2010, 2011; Keihaninejad et al, 2010; Kotrotsou et al, 2014; Svarer et al, 2005; Wang et al, 2012; Ledig et al, 2014), while other studies have focused on small sets or individual ROIs, such as the caudate nucleus (van Rikxoort et al, 2007b); the cerebellum (Park et al, 2014; Van Der Lijn et al, 2012; Weier et al, 2014); the amygdala (Hanson et al, 2012; Klein-Koerkamp et al, 2014); the corpus callosum (Ardekani et al, 2014; Gao et al, 2014; Meyer, 2014); the striatum (Janes et al, 2014); the subthalamic nucleus, red nucleus and substantia nigra (Xiao et al, 2014b,a); the ventricles (Chou et al, 2008; Raamana et al, 2014); and, most notably, the hippocampus, which has attracted much attention due to its association with dementia and Alzheimer’s disease (Akhondi-Asl et al, 2010; Bishop et al, 2010; Clerx et al, 2013; Hammers et al, 2007; Iglesias et al, 2010; Kim et al, 2012; Leung et al, 2010; Pipitone et al, 2014; Pluta et al, 2012; Raamana et al, 2014; van der Lijn et al, 2008; Van Der Lijn et al, 2012; Winston et al, 2013; Wolz et al, 2010b; Yushkevich et al, 2010; Platero et al, 2014; Ta et al, 2014). …”
Section: Survey Of Applicationsmentioning
confidence: 99%
“…III-B, we used all user interactions inserted on erroneous parts in the entire image to perform the segmentation editing. After the first round of editing, the DSC scores of most cases were higher than some inter-rater DSC scores reported in the literature [3840], and also had no notable qualitative errors. Thus, we usually performed only the first round of editing in this study.…”
Section: Resultsmentioning
confidence: 56%